If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 28 = 6x + 60 Reorder the terms: 28 + 2x = 6x + 60 Reorder the terms: 28 + 2x = 60 + 6x Solving 28 + 2x = 60 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 28 + 2x + -6x = 60 + 6x + -6x Combine like terms: 2x + -6x = -4x 28 + -4x = 60 + 6x + -6x Combine like terms: 6x + -6x = 0 28 + -4x = 60 + 0 28 + -4x = 60 Add '-28' to each side of the equation. 28 + -28 + -4x = 60 + -28 Combine like terms: 28 + -28 = 0 0 + -4x = 60 + -28 -4x = 60 + -28 Combine like terms: 60 + -28 = 32 -4x = 32 Divide each side by '-4'. x = -8 Simplifying x = -8
| -43=n-15 | | -70+3x=10x+28 | | 56=7(1+v)+7(v+7) | | 3x-6=3(x-1)-3 | | -10x+9=-6+3x | | 25a=6a | | 9=2z+1 | | 44=4(-8x-1)-8(x-1) | | 69=8*(-6)-3 | | 1.1-7.9-5.8x=7.28 | | 3x+3=10x-91 | | -25=-15t | | 8x-5=-7x+20 | | 4(m-10)=50 | | -x+2=-.6666666667x | | -12=n/6 | | 6y-2(2x+3y)=30 | | -2500-200x=-3000 | | -x+2=-.667x | | N+(-5)=3 | | 6(6m+8)-8(-1+8m)=56 | | x+9=4x+10 | | 9(v+8)=24 | | x-1.6/4=-3 | | log(y+2)=1.4 | | R=Cx+Ct | | 6(5+n)-2n-45+15=20 | | -6(2r+1)-7(-6r+8)=-2 | | 10=-5n | | y1/2x-1 | | 18-4(2x-2b)=5b-2x | | ln(y+2)=1.4 |